Answer:
y = 4x/3 - 1
Step-by-step explanation:
The slope-intercept form is represented generally as
y = mx + c
m is the slope of the line
c is the y-intercept
Given the equation, 8x - 6y = 6
We make y subject of formula
Step 1
Add 6y to both sides of the equation
8x - 6y + 6y = 6 + 6y
8x = 6 + 6y
Step 2
Subtract 6 from both sides of the equation
8x - 6 = 6 + 6y - 6
8x - 6 = 6y
6y = 8x - 6
Step 3
Divide each term on the left hand side and right hand side of equation by the coefficient of y = 6
6y/6 = 8x/6 - 6/6
y = 4x/3 - 1
y = mx + c ~ y = 4x/3 - 1
m = 4/3
c = -1
Therefore, the slope-intercept form of the equation of the line 8x – 6y = 6 is y = 4x/3 - 1